Let "x=e^t", then
"ln(x)=t"
Using chain rule:
"\\frac{\\partial z}{\\partial t}=\\frac{\\partial z}{\\partial x}\\frac{dx}{dt}=\\frac{\\partial z}{\\partial x}e^t"
"\\frac{\\partial z}{\\partial x}=\\frac{\\partial z}{\\partial t}e^{-t}"
"\\frac{\\partial ^2z}{\\partial t^2}=(\\frac{\\partial z}{\\partial x}e^t)'_t=\\frac{\\partial ^2z}{\\partial x^2}\\frac{dx}{dt}e^t+\\frac{\\partial z}{\\partial x}e^t=\\\\\n\\frac{\\partial ^2z}{\\partial x^2}e^{2t}+\\frac{\\partial z}{\\partial t}"
"\\frac{\\partial ^2z}{d\\partial ^2}=(\\frac{\\partial ^2z}{\\partial t^2}-\\frac{\\partial z}{\\partial t})e^{-2t}"
"x^2\\frac{\\partial ^2z}{\\partial x^2}+x\\frac{\\partial z}{\\partial x}=e^{2t}(\\frac{\\partial ^2z}{\\partial t^2}-\\frac{\\partial z}{\\partial t})e^{-2t}+e^t\\frac{\\partial z}{\\partial t}e^{-t}=\\\\\n\\frac{\\partial ^2z}{\\partial t^2}-\\frac{\\partial z}{\\partial t}+\\frac{\\partial z}{\\partial t}=\\frac{\\partial ^2z}{\\partial t^2}"
Similarly after substitution "y=e^s" we have
"y^2\\frac{\\partial ^2z}{d\\partial ^2}+y\\frac{\\partial z}{\\partial y}=\\frac{\\partial ^2z}{\\partial s^2}"
And equation becomes:
"\\frac{\\partial ^2z}{\\partial t^2}-\\frac{\\partial ^2z}{\\partial s^2}=t"
Now introduce new variables "\\xi=t+s,\\ \\eta=t-s"
"z=z(\\xi,\\eta)"
Using chain rule again:
"\\frac{\\partial z}{\\partial t}=\\frac{\\partial z}{\\partial \\xi}\\frac{\\partial \\xi}{\\partial t}+\\frac{\\partial z}{\\partial \\eta}\\frac{\\partial \\eta}{\\partial t}=\n\\frac{\\partial z}{\\partial \\xi}+\\frac{\\partial z}{\\partial \\eta}"
"\\frac{\\partial z}{\\partial s}=\\frac{\\partial z}{\\partial \\xi}\\frac{\\partial \\xi}{\\partial s}+\\frac{\\partial z}{\\partial \\eta}\\frac{\\partial \\eta}{\\partial s}=\n\\frac{\\partial z}{\\partial \\xi}-\\frac{\\partial z}{\\partial \\eta}"
"\\frac{\\partial ^2z}{\\partial t^2}=\\frac{\\partial ^2z}{\\partial \\xi^2}\\frac{\\partial \\xi}{\\partial t}+\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}\\frac{\\partial \\eta}{\\partial t}+\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}\\frac{\\partial \\xi}{\\partial t}+\\frac{\\partial ^2z}{\\partial \\eta^2}\\frac{\\partial \\eta}{\\partial t}="
"\\frac{\\partial ^2z}{\\partial \\xi^2}+2\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}+\\frac{\\partial ^2z}{\\partial \\eta^2}\\frac{\\partial \\eta}{\\partial t}"
"\\frac{\\partial ^2z}{\\partial s^2}=\\frac{\\partial ^2z}{\\partial \\xi^2}\\frac{\\partial \\xi}{\\partial s}+\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}\\frac{\\partial \\eta}{\\partial s}-(\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}\\frac{\\partial \\xi}{\\partial s}+\\frac{\\partial ^2z}{\\partial \\eta^2}\\frac{\\partial \\eta}{\\partial s})="
"\\frac{\\partial ^2z}{\\partial \\xi^2}-\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}-(\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}-\\frac{\\partial ^2z}{\\partial \\eta^2})=\n\\frac{\\partial ^2z}{\\partial \\xi^2}-2\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}+\\frac{\\partial ^2z}{\\partial \\eta^2})"
"\\frac{\\partial ^2z}{\\partial t^2}-\\frac{\\partial ^2z}{\\partial s^2}=4\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}"
"t=(t+s)\/2+(t-s)\/2=\\frac{\\xi+\\eta}{2}"
"4\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}=\\frac{\\xi+\\eta}{2}"
"\\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}=\\frac{\\xi+\\eta}{8}"
Integrating:
"\\frac {\\partial z}{\\partial \\eta}=\\int \\frac{\\partial ^2z}{\\partial \\xi \\partial \\eta}\\partial \\xi=\\int \\frac{\\xi+\\eta}{8}d\\xi=\\xi^2\/16+\\eta\\xi\/8+g(\\eta)"
"z=\\int (\\xi^2\/16+\\eta\\xi\/8+g(\\eta))d\\eta=\\\\\n\\xi^2\\eta\/16+\\eta^2\\xi\/16+G(\\eta)+F(\\xi)",
where F and G are arbitrary twice differentiable functions,
and G is antiderivative of g
Now use reverse substitutions "t=ln(x),\\ s=ln(y)"
we have:
"\\xi=t+s=ln(x)+ln(y)=ln(xy),\\\\\n \\eta=t-s=ln(x)-ln(y)=ln(x\/y)"
"z=\\frac{ln(xy)ln(x\/y)}{16}(ln(xy)+ln(x\/y))+G(ln(x\/y)+F(ln(xy))=\\\\\n\\frac{ln(xy)ln(x\/y)}{8}(ln(x))+G(ln(x\/y)+F(ln(xy))"
Answer: "z=\\frac{ln(xy)ln(x\/y)}{8}(ln(x))+G(ln(x\/y)+F(ln(xy))", where F and G are arbitrary twice differentiable functions.
Comments
Leave a comment